Teacher education in Pakistan - Khan, Akhter 1925- (University of the Philippines], 1959)
There is an urgent need for an investigation of the existing system of teacher education in Pakistan considering both the qualitative and quantitative aspects of the availability of teachers, in the light of the ideology of the country. Accordingly, this study examines the adequacy of teacher education in the country.